Blood Products Transfusion and Mid-Term Outcomes of Lung Transplanted Patients Under Extracorporeal Membrane Oxygenation Support. (December 2018) - Pettenuzzo, Tommaso; Faggi, Giulio; Di Gregorio, Guido; Schiavon, Marco; Marulli, Giuseppe; Gregori, Dario; Rea, Federico; Ori, Carlo; Feltracco, Paolo
Introduction: Extracorporeal membrane oxygenation (ECMO) is considered a reliable technique in lung transplantation requiring cardiorespiratory support. However, the impact of this technology on blood product transfusion rate and outcomes compared to off-pump lung transplantation has been rarely investigated. Methods: Between January 2012 and June 2015, 52 elective adult lung transplants were performed at our institution. Of these, 15 recipients required intraoperative venoarterial extracorporeal support and 37 did not. We compared blood product consumption and other outcome variables between the 2 groups. Results: We found comparable in-hospital (86.7% vs 97.3%, P = .14) and 6-month (86.7% vs 91.9%, P = .56) survival between patients with and without extracorporeal support, respectively. Survival at 30 days was lower in the ECMO group (86.7% vs 100%, P = .02). Although patients who underwent ECMO received more intraoperative transfusions, postoperative transfusion rate was similar between the 2 groups. The ECMO group experienced longer mechanical ventilation (median 3 vs 2 days, P = .02) and intensive care unit stay (median 7 vs 5 days, P = .02), besides more cardiogenic shock and deep vein thrombosis. However, we observed no difference in other major and minor in-hospital complications and 6-month complications. Conclusions: In our experience, despite the higher need for intraoperative transfusions, lung transplantation performed with ECMO support is comparable to the off-pump procedure as to short-term survival and outcomes.